Factors that influence the level of knowledge about the complications of abortion in university students - Bonilla-Crispin, Ángela (2018)
Introduction: In Perú, the abortion is the most frequent social problem in the adolescents, being the most affected the age group from 14 to 21 years old. The aim was to determine the association between the educational level of parents, family functionality and sources of information with the level of knowledge of the complications of abortion in women students of the faculties of accounting and nursing of the Hermilio Valdizan National University-Huanuco. Methods: It was carried out a descriptive cross-sectional study with a sample of 246 students, who met the inclusion and exclusion criteria. To collect data a questionnaire previously validated by experts was used. The statistical analysis used was Spss 15 (Mann-Whitney U). Results: From 246 students. The average age was 21.25 ± 1.8. Both level of education of parents and family functionality did not demonstrate a significant association with the level of knowledge of the complications of abortion, obtaining p = 0.479, p = 0.392 and p = 0.56, respectively. The 56,1% who obtained a high level of knowledge reported that they obtained information from both teachers as well as television, which had significant results (p = 0.01) and (p = 0.008). Conclusions: From this group of students, the factors that influence the level of knowledge about the complications of abortion were the sources of information, of all of them, teachers and television.